A comparison of discrete cosine transform and discrete wavelet transform algorithm in watermarking against common attacks - Said, Mohamed Abdisalan (2015)
Digital watermarking is a technique to embed additional data to digital images, audios and videos without affecting the quality of the original image. Watermark can be extracted for ownership verification or authentication. Currently, there is no comparison documented done between Discrete Cosine Transform (DCT) and Discrete Wavelet Transform (DWT). In this report, the DCT watermarking algorithms and DWT watermarking algorithms were compared based on robustness and imperceptibility criteria. With DCT, the watermark bits were embedded into the mid-band coefficients of the DCT in the cover image where the DWT algorithm was embedded the watermark bits into the horizontal and vertical sub-bands of DWT in the cover image. Experimental results had shown that the watermark is robust to geometric attacks and removal attacks. DCT and DWT are compared with regard to peak signal to noise ratio (PSNR), Mean Square Error (MSE) and Normalized Correlation (NC). The PSNR value of the watermarked Lena image in DWT is 47, higher than the DCT which is 44. The Normalized Correlation (NC) also had clarified that the extracted watermark in DWT 0.9964 is greater than the extracted watermark in DCT 0.2057. Thus, the results had indicated that the DWT gives better image quality than DCT.